Rationale and Design of a Panel Study Investigating Six Health Effects of Airborne Pollen: The EPOCHAL Study - Bürgler, Alexandra; Glick, Sarah; Hartmann, Karin; Eeftens, Marloes (Frontiers in Public Health, 2021)
Background While airborne pollen is widely recognized as a seasonal cause of sneezing and itchy eyes, its effects on pulmonary function, cardiovascular health, sleep quality, and cognitive performance are less well-established. It is likely that the public health impact of pollen may increase in the future due to a higher population prevalence of pollen sensitization as well as earlier, longer, and more intense pollen seasons, trends attributed to climate change. The effects of pollen on health outcomes have previously been studied through cross-sectional design or at two time points, namely preceding and within the period of pollen exposure. We are not aware of any observational study in adults that has analyzed the dose-response relationship between daily ambient pollen concentration and cardiovascular, pulmonary, cognitive, sleep, or quality of life outcomes. Many studies have relied on self-reported pollen allergy status rather than objectively confirming pollen sensitization. In addition, many studies lacked statistical power due to small sample sizes or were highly restrictive with their inclusion criteria, making the findings less transferable to the “real world”. Methods The EPOCHAL study is an observational panel study which aims to relate ambient pollen concentration to six specific health domains: 1) pulmonary function and inflammation; 2) cardiovascular outcomes (blood pressure and heart rate variability); 3) cognitive performance; 4) sleep; 5) health-related quality of life (HRQoL); and 6) allergic rhinitis symptom severity. Our goal is to enroll 400 individuals with diverse allergen sensitization profiles. The six health domains will be assessed while ambient exposure to pollen of different plants naturally varies: Health data will be collected through six home nurse visits (at approximately weekly intervals) as well as ten days of independent tracking of blood pressure, sleep, cognitive performance, HRQoL, and symptom severity by participants. Through repeated health assessments, we aim to uncover and characterize dose-response relationships between exposure to different species of pollen and numerous acute health effects, considering (non-)linearity, thresholds, plateaus and slopes. Conclusion A gain of knowledge in pollen-health outcome relationships is critical to inform future public health policies and will ultimately lead towards better symptom forecasts and improved personalized prevention and treatment.